Ankle Training With a Robotic Device Improves Hemiparetic Gait After a Stroke - Forrester, Larry W. (2010)
BACKGROUND: Task-oriented therapies such as treadmill exercise can improve gait velocity after stroke, but slow velocities and abnormal gait patterns often persist, suggesting a need for additional strategies to improve walking. OBJECTIVES: To determine the effects of a 6-week visually guided, impedance controlled, ankle robotics intervention on paretic ankle motor control and gait function in chronic stroke. METHODS: This was a single-arm pilot study with a convenience sample of 8 stroke survivors with chronic hemiparetic gait, trained and tested in a laboratory. Subjects trained in dorsiflexion–plantarflexion by playing video games with the robot during three 1-hour training sessions weekly, totaling 560 repetitions per session. Assessments included paretic ankle ranges of motion, strength, motor control, and overground gait function. RESULTS: Improved paretic ankle motor control was seen as increased target success, along with faster and smoother movements. Walking velocity also increased significantly, whereas durations of paretic single support increased and double support decreased. CONCLUSIONS: Robotic feedback training improved paretic ankle motor control with improvements in floor walking. Increased walking speeds were comparable with reports from other task-oriented, locomotor training approaches used in stroke, suggesting that a focus on ankle motor control may provide a valuable adjunct to locomotor therapies.